Lessons on bridging the science-policy divide for climate change action in developing countries - Cramer, Laura K.; Thornton, Philip K.; Dinesh, Dhanush; Jat, Mangi Lal; Khatri-Chhetri, Arun; Läderach, Peter R.D.; Martínez Barón, Deissy; Ouédraogo, Mathieu; Partey, Samuel T.; Totin, Edmond; Vasileiou, Ioannis; Veeger, Marieke (2018)
Decision makers in developing countries need evidence of the impacts climate change is having and will continue to have on agriculture and food systems as well as knowledge on how to design better policies to deal with such impacts. Research for development scientists are generating this evidence but it might not always be what decision makers want or need. We present here a synthesis that is an attempt to learn lessons from projects conducted by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). These projects engaged with policy makers and other stakeholders by providing climate science and spaces for dialogue between researchers and decision makers for the purpose of improving climate change and agricultural policies. This study draws conclusions from across projects in five regions and confirms the presence of similar enablers to policy engagement and constraints to the use of scientific findings by policy makers in each region. The paper is guided by the following research questions: (a) What are the most effective means of science-policy engagement in the areas of climate change, food security, and agriculture?; (b) What are the enabling factors for research uptake in decision making?; and (c) What are the main constraints to policy engagement, and how can they be overcome? The Kaleidoscope Model for agricultural and food security policy change is used throughout the paper to help organize results and conceptualize the process of policy change.